Governance challenges and resurgence of Igbo nationalism in Nigeria: Dissecting Indigenous People of Biafra (IPOB) - Godwin Onu; Amobi P. Chiamogu; Uchechukwu P. Chiamogu (Journal of Governance and Accountability Studies, 2022)
Purpose: The remote and immediate causes of the Nigerian civil war are rather deepening in the psyche of Ndi-Igbo in contemporary Nigerian politics and administration. Amidst the introduction of the Reconciliation, Reconstruction, and Rehabilitation (3Rs) policy over four (4) decades ago, the Ndi-Igbo are not just marginalized but alienated and separated from political power and its benefits in an ethnically and religiously deeply divided federation. More divesting wounds are flagrantly being inflicted upon the Igbo nation. The course pursued by secessionist Biafra between 1967-70 has continued to resonate in Movement for the Actualization of the Sovereign State of Biafra (MASSOB) and Indigenous People of Biafra (IPOB). This paper thus seeks to dissect the activities of IPOB in relation to national security in Nigeria. It also attempts a polemical analysis of IPOB as a separatist movement and the implications for the integration of Ndi-Igbo into the mainstream of Nigerian power politics. Research methodology: The paper adopts a qualitative research approach using an in-depth review of extant literature for informed comprehension of the dynamics of secession and unification in a deeply divided federal state of Nigeria. Using a theory of Secession: The Case for Political Self-Determination, the paper submits that treatments being meted out to the people of Igbo nation are compelling to separation. Results: It surmised that Ndi-Igbo is systematically sidelined and alienated from major political positions and that the allocation of key values is skewed against the Igbo nation. It thus recommends significant devolution of powers to foster an all-inclusive and participatory governance model. Recommendations: It also recommends the adoption and implementation of a balanced federalist accommodative principle for national cohesion, integration, and development of the Nigeria state.